EPEN-38. EZH2 INHIBITORY PROTEIN (EZHIP/Cxorf67) EXPRESSION IS HIGHLY CONCORDANT WITH H3K27me3 LOSS AND IS A PROMISING SURROGATE MARKER FOR POSTERIOR FOSSA TYPE A EPENDYMOMAS. (4th December 2020) - Nambirajan, Aruna; Rajeshwari, Madhu; Boorgula, Meher; Doddamani, Ramesh; Singh, Manmohan; Garg, Ajay; Suri, Vaishali; Sarkar, Chitra; Sharma, Mehar
Abstract: BACKGROUND: Gene expression and DNA methylation have identified 2 distinct clinicopathological subgroups among the WHO Grade II/III posterior fossa (PF) ependymomas (EPN), of which the PF-A molecular subgroup associates with poor outcome. OBJECTIVE: To analyse the utility of immunohistochemistry for H3K27me3, Tenascin C, EZHIP (Cxorf67), EZH2 and fluorescence-in-situ-hybridisation for chromosome 1q21 locus gain in the prognostic stratification of PF-EPNs. METHODS: All PF Grade II/III tumors were retrieved (2009–2019). Immunohistochemistry for H3K27me3, H3K27M-mutation-specific antibody, EZH2, EZHIP, Tenascin-C and fluorescence in-situ hybridisation for 1q21 locus was performed and compared with outcome. RESULTS: 71 PF-EPNs were included. H3K27me3 loss (PF-A) was seen in 65% (46/71) of cases, of which majority were positive for EZHIP (73%, 24/33) and Tenascin C (65%, 28/43). Minority showed chromosome 1q gain (19%, 8/42). An EZHIP negative PF-A tumor was immunopositive for H3K27M-mutant staining, while all others were negative. PF-A EPNs occurred at a median age of 4.5 years (range 1–53), were predominantly grade III (Grade III:II – 1.6:1), and 50% (10/20) of patients on follow-up experienced tumor progression. EPNs with retained H3K27me3 (PF-B) did not show EZHIP expression (0/20) or 1q gain; however, tenascin C expression was seen in 47% (8/25) of them. They occurred predominantly in adults, showed Grade II preponderance and only 2/11 patients on follow-up experienced progression. EZH2 expression did not correlate with H3K27me3 loss but positively correlated with EZHIP expression (p=0.015). CONCLUSION: H3K27me3 is a reliable surrogate for prognostic classification of PF-EPNs. EZHIP expression is highly concordant with H3K27me3 loss and is a valuable adjunct.